A high-solid flake heavy-duty anticorrosive coating for buried metal components and preparation method thereof

By developing a high-solid scale heavy anticorrosion coating, the problem of the limited formation of a long-term anticorrosion coating on the surface of metal components is solved, and a long-term anticorrosion coating is achieved on the surface of metal surfaces, with excellent anticorrosion effect and high safety.

CN118725692BActive Publication Date: 2025-04-15NINGBO FEIJIAO MFG PAINT
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410995184.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-24
Publication Date
2025-04-15
Estimated Expiration
2044-07-24

AI Technical Summary

Technical Problem

Traditional anti-rust and anti-corrosion paint forms a long-term anti-corrosion coating on the surface of metal components, and requires frequent inspection and repair, especially in underground hidden projects and buried metal component pipelines, which are difficult, costly and have a negative impact on the environment.

Method used

A high-solid scale heavy anticorrosion coating for buried metal components was developed, including components A and components B. Component A contains epoxy resin, anti-rust pigment, scale materials, fillers and additives, and component B contains curing agents, additives and solvents. Through reasonable components and processes, a multi-layer scale structure coating is formed, which has excellent anti-corrosion effect.

Benefits of technology

The paint forms a long-term anticorrosion coating on the metal surface, which can be operated in harsh environments for more than ten or even decades without repair and re-coating. It has high density and strong sealing properties, reducing the harm of the paint to the human body and the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004959957500000111
    Figure BDA0004959957500000111
  • Figure BDA0004959957500000191
    Figure BDA0004959957500000191
  • Figure BDA0004959957500000201
    Figure BDA0004959957500000201
Patent Text Reader

Abstract

The present invention belongs to the technical field of chemical coatings, and specifically relates to a high-solid flake heavy anti-corrosion coating for buried metal components and a preparation method thereof. The coating comprises component A and component B; the component A comprises the following components by mass fraction: 30-50% epoxy resin, 10-30% anti-rust pigment, 10-30% flake material, 5-15% filler, 0-10% auxiliary agent A, and the balance is solvent A; the component B comprises the following components by mass fraction: 50-70% curing agent, 0-15% auxiliary agent B, and the balance is solvent B; wherein the anti-rust pigment comprises zinc powder. The coating of the present invention not only has excellent anti-corrosion performance, but also has strong film adhesion, good impact resistance and chemical resistance, and the product has high solid content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical coatings, and in particular relates to a high-solid flake heavy-duty anticorrosive coating for buried metal components and a preparation method thereof. Background Art

[0002] With the sustained development of the national economy and infrastructure, the requirements for corrosion protection of national key projects and large-scale projects are becoming increasingly higher, especially for large steel components and equipment, bridges, pipelines, storage tanks, marine engineering facilities, docks, derricks and other infrastructure and structures, which have put forward higher requirements for coatings; there are more and more "century-old" long-term anti-corrosion projects.

[0003] Traditional anti-rust and anti-corrosion paints have limited ability to form long-term anti-corrosion coatings on the surface of metal components, and measures such as repairs or repainting must be taken every once in a while to prevent steel from rusting and corroding. Repairs and repainting must be carried out on a large scale, and surface treatment cannot be performed due to complex metal special-shaped component projects. These problems have brought great difficulties to construction, especially underground concealed projects, buried pipelines, and metal component embedded parts, which are more difficult to repair and replace. In addition to high maintenance costs, they also have a negative impact on the environment. Therefore, it is imperative to develop long-term anti-corrosion coatings. Summary of the invention

[0004] The purpose of the present invention is to provide a new high-solid flake heavy-duty anti-corrosion coating for buried metal components, as well as a preparation method and application. The coating has excellent anti-corrosion effect when applied to the surface of rust-prone steel structures and buried metal component pipelines, and can meet the long-term anti-corrosion and special needs of metal anti-corrosion coatings in special harsh environments.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a high-solid flake heavy-duty anti-corrosion coating for buried metal components, the coating comprising component A and component B;

[0006] The component A comprises the following components by mass fraction: 30-50% epoxy resin, 10-30% anti-rust pigment, 10-30% flake material, 5-15% filler, 0-10% additive A, and the balance is solvent A;

[0007] The B component includes the following components by mass fraction: 50-70% of curing agent, 0-15% of auxiliary agent B, and the balance of solvent B;

[0008] Wherein, the anti-rust pigment includes zinc powder.

[0009] In the present invention, auxiliary agent A and auxiliary agent B are only used to distinguish whether they are present in component A or component B, and have no special meaning. Similarly, solvent A and solvent B are only used to distinguish whether they are present in component A or component B, and have no special meaning.

[0010] In order to make the components in the system more compatible, the A component further includes the following components in mass fractions: 35-40% epoxy resin, 17-21% anti-rust pigment, 17-21% flake material, 8-10% filler, 2-4% auxiliary agent A, and the balance is solvent A; the B component includes the following components in mass fractions: 55-60% curing agent, 8-12% auxiliary agent B, and the balance is solvent B.

[0011] Epoxy resin

[0012] The epoxy resin is a base material of the coating, and further, the epoxy resin is a bisphenol A epoxy resin.

[0013] Furthermore, the bisphenol A epoxy resin includes bisphenol A liquid epoxy resin and bisphenol A solvent-diluted epoxy resin. Preferably, the mass ratio of the bisphenol A liquid epoxy resin to the bisphenol A solvent-diluted epoxy resin is 1:(0.5-1.5), for example, 1:0.5, 1:0.7, 1:0.9, 1:1.3, 1:1.5, and preferably 1:(1-1.4).

[0014] Bisphenol A solvent-diluted epoxy resin refers to a semi-solid epoxy resin or a solid epoxy resin dispersed in a corresponding solvent. In the prior art, bisphenol A solvent-diluted epoxy resin has excellent adhesion and can increase the adhesion of the coating on the metal. Bisphenol A solvent-diluted epoxy resin generally contains an organic solvent. During the experiment, in order to reduce the VOC content in the coating, the inventor used bisphenol A liquid epoxy resin to replace part of the bisphenol A solvent-diluted epoxy resin. It was unexpectedly found that in the system of the present invention, the inventor found that the use of bisphenol A liquid epoxy resin and bisphenol A solvent-diluted epoxy resin as the base material of the coating in the present invention can further increase the adhesion of the coating compared with a single bisphenol A solvent-diluted epoxy resin. This may be because the two work together to promote the dispersion of fillers, flake materials and anti-rust pigments in the system on the one hand, and on the other hand, to promote the emulsion particles formed by the coating during coating to be more moderate, which can better increase the adhesion and uniformity of the coating.

[0015] Furthermore, the difference in softening point between the bisphenol A epoxy resin and the bisphenol A solvent-diluted epoxy resin is 20-60°C, for example, 10°C, 15°C, 20°C, 21°C, 237°C, 24°C, 26°C, 28°C, 41°C, 55°C, and 60°C.

[0016] Furthermore, the softening point of the bisphenol A type liquid epoxy resin is 10-30°C, preferably 12-20°C.

[0017] The bisphenol A liquid epoxy resin in the present invention can be obtained commercially. Examples of the bisphenol A liquid epoxy resin include YPE6101 produced by Shanghai Yuanbang Resin Factory, SM6101 (99%) epoxy resin liquid produced by Jiangsu Sanmu Group Corporation, and CYD6101 produced by Baling Petrochemical Company.

[0018] Furthermore, the softening point of the bisphenol A solvent-diluted epoxy resin is 50-80°C, preferably 60-78°C.

[0019] Furthermore, the solid content of the bisphenol A solvent-diluted epoxy resin is 70-80%, for example, 70%, 75%, or 85%.

[0020] The bisphenol A solvent-diluted epoxy resin in the present invention can be obtained from the market, such as YPE-011X75 produced by Shanghai Yuanbang Resin Factory, SM601-75 produced by Jiangsu Sanmu Group Company, and CYD601-75 produced by Baling Petrochemical Company.

[0021] Anti-rust pigment

[0022] The anti-rust pigment refers to a substance with an anti-rust effect. Furthermore, the average particle size of the zinc powder is 800-1200 meshes. The zinc powder in the present invention can be obtained commercially, such as 1000 mesh zinc powder from Jiangsu Yangzhou Shuangsheng Zinc Powder Factory.

[0023] Furthermore, the anti-rust pigment also includes ferrophosphorus powder, zinc phosphate, zinc strontium phosphate and aluminum tripolyphosphate.

[0024] Furthermore, the average particle size of the ferrophosphorus powder is 500-1000 mesh.

[0025] Furthermore, the mass ratio of the zinc powder, ferrophosphorus powder, zinc phosphate, zinc strontium phosphate and aluminum tripolyphosphate is 1: (0.1-0.5): (0.1-0.5), (0.3-0.7): (0.2-0.6), preferably 1: (0.2-0.3): (0.3-0.4), (0.4-0.5): (0.3-0.4), and further preferably 1: 0.25: 0.375: 0.475: 0.375.

[0026] After a large number of research and development tests, the inventors found that in the overall system of the present invention, the use of the above-mentioned several specific anti-rust pigments synergistically has a better anti-rust effect. This may be because the above-mentioned several specific anti-rust pigments can jointly exert an anti-corrosion effect from the three aspects of synergistic physics, chemistry and electrochemistry in the coating system of the present invention.

[0027] The specific anti-corrosion raw materials in the present invention can be obtained commercially, for example, ferrophosphorus powder and zinc phosphate can be purchased from Henan Huijin Company; zinc strontium phosphate can be purchased from D900 zinc strontium phosphate of Shanghai Junjiang Technology Co., Ltd.; aluminum tripolyphosphate can be purchased from JP-B800 high-purity aluminum tripolyphosphate of Shanghai Junjiang Technology Co., Ltd.

[0028] Flake material

[0029] The flake material generally presents a hierarchical structure, consisting of a plurality of thin sheets or stacked layers. Furthermore, the flake material includes an inorganic non-metallic flake material or a modified product thereof, and a metallic flake material or a modified product thereof.

[0030] Furthermore, the mass ratio of the inorganic non-metallic flake material or its modified product to the metallic flake material or its modified product is (1-3):1, preferably (1.5-2.5):1, for example, 1.5:1, 1.6:1, 1.8:1, 1.9:1, 2:1.

[0031] In the present invention, after a large number of research and development tests, the inventors found that when inorganic non-metallic flake materials or their modified products are used and metallic flake materials or their modified products coexist in the system, the corrosion resistance and wear resistance of the coating can be better increased. This may be because different types of flake materials can better form a "maze" in the system, hindering external substances from entering the interior of the coating. The two work synergistically with their components in the system to better improve the presence of the hard phase.

[0032] Furthermore, the flake material includes a modified product of an inorganic non-metallic flake material and a modified product of a metallic flake material, and both the modified product of the inorganic non-metallic flake material and the modified product of the metallic flake material are modified with dopamine-type polyacrylate.

[0033] In the present invention, it can be understood that the modified inorganic non-metallic flake material is a dopamine-type polyacrylate-modified inorganic non-metallic flake material, and the modified metal-type flake material is a dopamine-type polyacrylate-modified metal-type flake material. Because the modified materials are the same, the present invention can directly prepare the dopamine-type polyacrylate-modified flake material, that is, the preparation method of the modified inorganic non-metallic flake material and the modified metal-type flake material is:

[0034] S1, under N2 protection, mixes acrylic acid monomer, dopamine methacrylamide, N,N-dimethylformyl and initiator, and then reacts at 70-80°C for 4-6 hours to obtain a prepolymer;

[0035] S2: Mix inorganic non-metallic flake material, metallic flake material, N,N-dimethylformyl and 0.2-0.5 mol / L phosphoric acid aqueous solution, and then react at 70-80°C for 1-3 hours, then add prepolymer and heat to 150-160°C and react for 30-60 minutes, then cool, filter and dry to constant weight to obtain.

[0036] Existing epoxy resin coatings have good adhesion themselves, but the addition of components such as flake materials will affect their adhesion, because the compatibility of components such as flake materials with epoxy resin is not good, which will reduce their adhesion. At present, coupling agents are generally added to the coating to modify its compatibility, but the amount of coupling agent added cannot be too large. Too much will affect the comprehensive performance of the coating, and the system contains not only inorganic components such as flake materials, but also inorganic components such as fillers. The coupling agent cannot improve its compatibility to a large extent. In the present invention, after a large number of research and development experiments, the inventors found that the dopamine-type polyacrylate-modified flake material can not only increase the adhesion of the coating, but also increase the storage stability and impact strength of the coating. This may be because the dopamine-type polyacrylate-modified flake material can be well dispersed in the epoxy resin system, and the dopamine-type polyacrylate-modified flake material and other components in the system can form a uniform and dense cross-linked network structure. The network avoids the problem that the micro-nano structure of the coating is damaged under the impact of external forces, making it denser and better able to improve wear resistance and impact strength.

[0037] Furthermore, in step S1, the mass ratio of the acrylic acid monomer, dopamine methacrylamide, N,N-dimethylformyl and initiator is 1:(0.5-0.6):(15-20):(0.1-0.2), preferably 1:0.55:18:0.15.

[0038] Furthermore, in step S1, the acrylic monomer is selected from butyl acrylate and / or methyl methacrylate, preferably butyl acrylate.

[0039] The inventors have found that the comprehensive properties of the coating can be better improved when butyl acrylate is used.

[0040] Furthermore, in step S1, the initiator is selected from at least one of ammonium persulfate, benzoyl peroxide, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate and azobisisobutyronitrile, preferably azobisisobutyronitrile.

[0041] Furthermore, in step S2, the mass ratio of the total mass of the inorganic non-metallic flake material and the metallic flake material to the mass of N,N-dimethylformyl, the aqueous phosphoric acid solution, and the prepolymer is (8-12):(20-40):(10-30):100, preferably 10:30:20:100.

[0042] Furthermore, the inorganic non-metallic flake material is selected from glass flakes and graphite flake powder, and the weight ratio thereof is 1:(0.2-0.5), preferably 1:(0.2-0.4), and further preferably 1:0.35.

[0043] Furthermore, the average particle size of the glass flakes is 500-700 mesh, and the average particle size of the graphite flake powder is 700-900 mesh.

[0044] The glass flakes and graphite flake powder in the present invention can be obtained commercially, for example, glass flakes are purchased from Nanjing Nuowei Fine Powder Industry Co., Ltd., and graphite flake powder is purchased from Zhejiang Kainuoen New Materials.

[0045] Furthermore, the metal flake material is selected from mica iron oxide and aluminum powder slurry, and the mass ratio thereof is (1-5):1, preferably (2-3):1, and further preferably 2.5:1.

[0046] Furthermore, the average particle size of the mica iron oxide is 200-1000 mesh, preferably 300-500 mesh.

[0047] The mica iron oxide and aluminum slurry in the present invention can be obtained from the market, for example, the mica iron oxide is purchased from 400 mesh mica iron oxide of Henan Huijin Company, and the aluminum slurry is purchased from N110 aluminum slurry of Anhui Xuyang Group.

[0048] filler

[0049] Furthermore, the filler is selected from at least one of quartz powder, heavy calcium powder, talcum powder, barium sulfate, titanium dioxide and titanium dioxide, preferably precipitated barium sulfate, talcum powder and titanium dioxide, and the mass ratio thereof is preferably (0.5-1.5):(0.5-1.5):1, preferably (0.6-0.8):(0.6-0.8):1.

[0050] The particle size of the filler component in the present invention is the size of the filler component commonly used in coatings, and the present invention has no special limitation on this. For example, the average particle size of precipitated barium sulfate is 600-1000 mesh, the talc powder can be nanometer-grade, for example, 10-30nm, and the titanium dioxide is the commonly used 218 titanium dioxide.

[0051] The filler in the present invention can be obtained from the market, for example, precipitated barium sulfate is purchased from Hubei Gucheng Xinhe Co., Ltd., and talc powder is purchased from Guangxi Guilin Longsheng Talc Powder Factory.

[0052] Curing agent

[0053] Furthermore, the curing agent is selected from aliphatic amine epoxy curing agent and / or polyamide epoxy curing agent.

[0054] Furthermore, the curing agent is selected from aliphatic amine epoxy curing agent and polyamide epoxy curing agent, and the mass ratio thereof is (0.5-1):1, for example, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1.

[0055] Furthermore, the amine value of the fatty amine epoxy curing agent is 500-600 mgKOH / g.

[0056] The fatty amine epoxy curing agent in the present invention can be obtained from the market, for example, 593 fatty amine epoxy curing agent produced by Wuxi Pinhua Chemical Company.

[0057] Furthermore, the amine value of the polyamide epoxy curing agent is 200-240 mgKOH / g.

[0058] The polyamide epoxy curing agent in the present invention can be obtained from the market, for example, 650 polyamide epoxy curing agent produced by Jiangsu Changjiang Chemical Company.

[0059] Additive A, Additive B

[0060] In the present invention, the type of auxiliary agent can be selected according to the needs, such as coupling agent, anti-settling thixotropic agent, dispersant, UV protection auxiliary agent, accelerator.

[0061] Furthermore, the auxiliary agent A and the auxiliary agent B are each independently selected from at least one of a coupling agent, an anti-settling thixotropic agent, a dispersant, an anti-ultraviolet auxiliary agent and an accelerator.

[0062] The coupling agent, anti-settling thixotropic agent, dispersant, UV protection agent and leveling agent in the present invention can all be conventional types in the art. For example, the coupling agent can be KH-550 coupling agent, the anti-settling thixotropic agent can be BENGEL 828 anti-settling thixotropic agent, 108 organic bentonite, the UV protection agent can be UV1000TF UV protection agent, the dispersant can be BYK-104S dispersant, and the accelerator can be DMP-30 accelerator.

[0063] Furthermore, the auxiliary agent A is BENGEL 828 anti-settling thixotropic agent, 108 organic bentonite, and BYK-104S dispersant, and the mass ratio thereof is (0.5-1):(0.2-0.5):1.

[0064] Furthermore, the auxiliary agent B is KH-550 coupling agent, UV1000TF anti-ultraviolet auxiliary agent, and DMP-30 accelerator, and the mass ratio thereof is (0.3-0.5):(0.5-0.7):1.

[0065] Solvent A, Solvent B

[0066] Furthermore, the solvent A and the solvent B are each independently selected from at least one of a reactive diluent, an aromatic hydrocarbon solvent and an alcohol solvent.

[0067] The active diluent may be any conventional type in the art, such as LI TE513 active diluent.

[0068] Furthermore, the aromatic hydrocarbon solvent is selected from at least one of benzene, toluene and xylene, preferably xylene.

[0069] Furthermore, the alcohol solvent is selected from at least one of ethanol, methanol, propanol, n-butanol and ethylene glycol, preferably n-butanol.

[0070] Furthermore, the solvent A is selected from LI TE513 active diluent, xylene and n-butanol, and the mass ratio thereof is 7:2:1.

[0071] Furthermore, the solvent B is selected from xylene and n-butanol, and the mass ratio thereof is 7:3.

[0072] Furthermore, the mass ratio of component A to component B is (4-6):1, preferably 5:1.

[0073] The second aspect of the present invention provides a method for preparing the high-solid flake heavy-duty anticorrosion coating for buried metal components, the preparation method comprising:

[0074] (1) Solvent A is divided into two parts, and the mass ratio of the first part to the second part is (3-4):1. The first part of solvent A, epoxy resin, anti-rust pigment, flake material, filler, and additive A are dispersed by sand milling until the particle size is ≤50 μm, and then the sand milling dispersion is stopped. Then, the second part of solvent A is added and mixed to obtain component A;

[0075] (2) The curing agent, the auxiliary agent B and the solvent are dispersed for the second time, and then filtered using a 100-150 mesh filter to obtain component B.

[0076] Furthermore, in step (1), the first dispersing conditions include stirring at 800-850 rpm for 30-45 min.

[0077] In step (1), there is no particular limitation on the mixing conditions as long as the mixture can be mixed evenly.

[0078] Furthermore, in step (2), the conditions for the second dispersion include: stirring at 60-80 rpm for 20-40 min.

[0079] When the coating of the present invention is used, component A and component B can be mixed according to a weight ratio, stirred evenly, and matured for 10-15 minutes before being used up within 4 hours.

[0080] Compared with the prior art, the coating of the present invention has at least the following beneficial effects:

[0081] 1. The multi-layer flake structure coating formed in the coating formed by the high-solid flake heavy anti-corrosion coating for buried metal components has corrosion inhibition performance. Through the reasonable organization of flake materials, anti-rust pigments, fillers and epoxy resins, the coating density can be better increased, and the shielding effect on the closed metal surface is better. The synergistic effect of non-organic non-metallic flake materials such as graphite flakes and metal flake materials such as mica iron oxide and anti-rust pigments in the system can make the cathodic anti-corrosion synergistic effect more perfect, and have excellent salt spray resistance, so that the coating of the present invention has high coating density and strong sealing, and can establish a long-term anti-corrosion coating system and shielding effect on the metal surface. After coating with (epoxy coal tar heavy anti-corrosion coating) for large steel components, equipment, bridges, pipelines, oil tanks, buried metal components, pipelines and other facilities, the coating is firmly attached to the metal surface and can operate in harsh environments for more than ten years or even decades without maintenance or re-coating.

[0082] 2. The buried metal components in the present invention use high-solid flake heavy-duty anti-corrosion coatings, which have the characteristics of low organic solvent content, solid content ≧90%, thick paste type, and low VOC emissions. At the same time, the coating has higher safety during storage and transportation, and also reduces the hazards of the coating to the human body and the environment. DETAILED DESCRIPTION

[0083] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0084] In the following examples and comparative examples, the sources of raw materials are shown in Table 1. Unless otherwise specified, the remaining raw materials can be obtained from commercial sources.

[0085] Table 1

[0086]

[0087] Example 1

[0088] This embodiment provides a high-solid flake heavy-duty anti-corrosion coating for buried metal components, the coating comprising component A and component B:

[0089] The component A comprises the following components by mass fraction: 38% epoxy resin, 19.8% anti-rust pigment, 20.5% flake material, 9.8% filler, 2.8% additive A, and the balance is solvent A;

[0090] The B component includes the following components by mass fraction: 58% curing agent, 10% auxiliary agent B, and the balance is solvent B;

[0091] The epoxy resin is a bisphenol A epoxy resin; the bisphenol A epoxy resin is a bisphenol A liquid epoxy resin and a bisphenol A solvent-diluted epoxy resin, and the mass ratio thereof is 1:1.375; the softening point of the bisphenol A liquid epoxy resin is 16±4°C, and its model is YPE6101 produced by Shanghai Yuanbang Resin Factory; the softening point of the bisphenol A solvent-diluted epoxy resin is 68±8°C, and its model is YPE-011X75 produced by Shanghai Yuanbang Resin Factory;

[0092] The anti-rust pigment is 1000 mesh zinc powder, ferrophosphorus powder (800 mesh), zinc phosphate, D900 zinc strontium phosphate and JP-B800 high purity aluminum tripolyphosphate, and the mass ratio is 1:0.25:0.375:0.475:0.375;

[0093] The preparation method of the flake material is:

[0094] S1, under N2 protection, mixed butyl acrylate, dopamine methacrylamide, N,N-dimethylformyl and initiator in a mass ratio of 1:0.55:18:0.15, and then reacted at 75°C for 5 hours to obtain a prepolymer;

[0095] S2: Inorganic non-metallic flake material (600 mesh glass flake and 800 mesh graphite flake powder, with a weight ratio of 1:0.35), metal flake material (400 mesh mica iron oxide and aluminum powder slurry, with a mass ratio of 2.5:1), N,N-dimethylformyl, and 0.25 mol / L phosphoric acid aqueous solution are mixed, reacted at 75°C for 2 hours, then the prepolymer is added and the temperature is raised to 160°C for reaction for 50 minutes, then cooled, filtered, and dried to constant weight to obtain the flake material;

[0096] The mass ratio of the inorganic non-metallic flake material, the metallic flake material, N,N-dimethylformyl, 0.25 mol / L phosphoric acid aqueous solution and the prepolymer is 6.6:3.4:30:20:100;

[0097] The initiator is azobisisobutyronitrile;

[0098] The filler is selected from precipitated barium sulfate, talcum powder and titanium dioxide, and the mass ratio thereof is 0.79:0.79:1; the average particle size of the precipitated barium sulfate is 625 mesh; the average particle size of the nano-grade talcum powder is 10nm;

[0099] The curing agent is selected from aliphatic amine epoxy curing agent and polyamide epoxy curing agent, and the mass ratio thereof is 0.76:1; the amine value of the aliphatic amine epoxy curing agent is 550 mgKOH / g, which is 593 aliphatic amine epoxy curing agent produced by Wuxi Pinhua Chemical Company; the amine value of the polyamide epoxy curing agent is 220 mgKOH / g, which is 650 polyamide epoxy curing agent produced by Jiangsu Changjiang Chemical Company.

[0100] The auxiliary agent A is BENGEL 828 anti-settling thixotropic agent, 108 organic bentonite, and BYK-104S dispersant, and the mass ratio thereof is 0.77:0.38:1;

[0101] The auxiliary agent B is KH-550 coupling agent, UV1000TF anti-ultraviolet auxiliary agent, and DMP-30 accelerator, and the mass ratio thereof is 0.4:0.6:1;

[0102] The solvent A is selected from LI TE513 active diluent, xylene and n-butanol, and the mass ratio thereof is 7:2:1;

[0103] The solvent B is selected from xylene and n-butanol, and the mass ratio thereof is 7:3;

[0104] The preparation method of high-solid flake heavy-duty anticorrosive coating for buried metal components comprises the following steps:

[0105] (1) Solvent A is divided into two parts, with the mass ratio of the first part to the second part being 3.3:1. The first part of solvent A, epoxy resin, anti-rust pigment, flake material, filler, and additive A are dispersed by sand milling until the particle size is ≤50 μm, and then the sand milling dispersion is stopped. Then, the second part of solvent A is added and mixed to obtain component A;

[0106] (2) performing a second dispersion of the curing agent, the auxiliary agent B and the solvent, and then filtering with a 120-mesh filter to obtain component B;

[0107] In step (1), the first dispersing conditions include: stirring at 800 rpm for 35 min;

[0108] In step (2), the conditions for the second dispersion include: stirring at 70 rpm for 30 min;

[0109] The mass ratio of component A to component B is 5:1.

[0110] Example 2

[0111] This embodiment provides a high-solid flake heavy-duty anti-corrosion coating for buried metal components, the coating comprising component A and component B:

[0112] The component A comprises the following components by mass fraction: 35% epoxy resin, 17.6% anti-rust pigment, 21% flake material, 8% filler, 4% additive A, and the balance solvent A;

[0113] The B component includes the following components by mass fraction: 55% curing agent, 8% auxiliary agent B, and the balance solvent B;

[0114] The epoxy resin is a bisphenol A epoxy resin; the bisphenol A epoxy resin includes a bisphenol A liquid epoxy resin and a bisphenol A solvent-diluted epoxy resin, with a mass ratio of 1:1; the softening point of the bisphenol A liquid epoxy resin is 16±4°C, and its model is SM6101 (99%) epoxy resin liquid produced by Jiangsu Sanmu Group Co., Ltd.; the softening point of the bisphenol A solvent-diluted epoxy resin is 68±8°C, and its model is SM601-75 produced by Jiangsu Sanmu Group Co., Ltd.;

[0115] The anti-rust pigment includes 1000 mesh zinc powder, ferrophosphorus powder (800 mesh), zinc phosphate, D900 zinc strontium phosphate and JP-B800 high-purity aluminum tripolyphosphate, and the mass ratio thereof is 1:0.3:0.4:0.5:0.4;

[0116] The preparation method of the flake material is as follows:

[0117] S1, under N2 protection, mixed butyl acrylate, dopamine methacrylamide, N,N-dimethylformyl and initiator in a mass ratio of 1:0.6:20:0.1, and then reacted at 75°C for 5 hours to obtain a prepolymer;

[0118] S2: Inorganic non-metallic flake material (600 mesh glass flake and 800 mesh graphite flake powder, with a weight ratio of 1:0.3), metal flake material (400 mesh mica iron oxide and aluminum powder slurry, with a mass ratio of 3:1), N,N-dimethylformyl, and 0.25 mol / L phosphoric acid aqueous solution are mixed, reacted at 75°C for 2 hours, then the prepolymer is added and the temperature is raised to 160°C for reaction for 50 minutes, then cooled, filtered, and dried to constant weight to obtain a dopamine-type polyacrylate modified product;

[0119] The mass ratio of the inorganic non-metallic flake material, the metallic flake material, N,N-dimethylformyl, 0.25 mol / L phosphoric acid aqueous solution and the prepolymer is 6:4:20:30:100;

[0120] The initiator is azobisisobutyronitrile;

[0121] The filler is selected from precipitated barium sulfate, talcum powder and titanium dioxide, and the mass ratio thereof is 0.6:0.8:1; the average particle size of the precipitated barium sulfate is 625 mesh; the average particle size of the nano-grade talcum powder is 10nm;

[0122] The curing agent is selected from aliphatic amine epoxy curing agent and polyamide epoxy curing agent, and the mass ratio thereof is 0.7:1; the amine value of the aliphatic amine epoxy curing agent is 550 mgKOH / g, which is 593 aliphatic amine epoxy curing agent produced by Wuxi Pinhua Chemical Company; the amine value of the polyamide epoxy curing agent is 220 mgKOH / g, which is 650 polyamide epoxy curing agent produced by Jiangsu Changjiang Chemical Company.

[0123] The auxiliary agent A is BENGEL 828 anti-settling thixotropic agent, 108 organic bentonite, and BYK-104S dispersant, and the mass ratio thereof is 0.75:0.4:1;

[0124] The auxiliary agent B is KH-550 coupling agent, UV1000TF anti-ultraviolet auxiliary agent, and DMP-30 accelerator, and the mass ratio thereof is 0.3:0.5:1;

[0125] The solvent A is selected from LI TE513 active diluent, xylene and n-butanol, and the mass ratio thereof is 7:2:1;

[0126] The solvent B is selected from xylene and n-butanol, and the mass ratio thereof is 7:3;

[0127] The preparation method of high-solid flake heavy-duty anticorrosive coating for buried metal components comprises the following steps:

[0128] (1) Solvent A is divided into two parts, with the mass ratio of the first part to the second part being 3.3:1. The first part of solvent A, epoxy resin, anti-rust pigment, flake material, filler, and additive A are dispersed by sand milling until the particle size is ≤50 μm, and then the sand milling dispersion is stopped. Then, the second part of solvent A is added and mixed to obtain component A;

[0129] (2) performing a second dispersion of the curing agent, the auxiliary agent B and the solvent, and then filtering with a 120-mesh filter to obtain component B;

[0130] In step (1), the first dispersing conditions include: stirring at 800 rpm for 35 min;

[0131] In step (2), the conditions for the second dispersion include: stirring at 70 rpm for 30 min;

[0132] The mass ratio of component A to component B is 5:1.

[0133] Example 3

[0134] The method according to Example 1 is different in that:

[0135] The model of the bisphenol A type liquid epoxy resin is CYD6101 produced by Baling Petrochemical Company, and the model of the bisphenol A solvent-diluted epoxy resin is CYD601-75 produced by Baling Petrochemical Company.

[0136] Comparative Example 1

[0137] The method according to Example 1 is different in that:

[0138] The flake material is an inorganic non-metallic flake material and a metallic flake material, and the mass ratio thereof is 6.6:3.4; the inorganic non-metallic flake material is 600 mesh glass flake and 800 mesh graphite flake powder, and the weight ratio thereof is 1:0.35; the metallic flake material is 400 mesh mica iron oxide and aluminum powder slurry, and the mass ratio thereof is 2.5:1.

[0139] Comparative Example 2

[0140] The method according to Example 2 is different in that:

[0141] The flake material is an inorganic non-metallic flake material and a metallic flake material, and the mass ratio thereof is 6.6:3.4; the inorganic non-metallic flake material is 600 mesh glass flake and 800 mesh graphite flake powder, and the weight ratio thereof is 1:0.35; the metallic flake material is 400 mesh mica iron oxide and aluminum powder slurry, and the mass ratio thereof is 2.5:1.

[0142] Comparative Example 3

[0143] The method of Example 3 is different in that:

[0144] The flake material is an inorganic non-metallic flake material and a metallic flake material, and the mass ratio thereof is 6.6:3.4; the inorganic non-metallic flake material is 600 mesh glass flake and 800 mesh graphite flake powder, and the weight ratio thereof is 1:0.35; the metallic flake material is 400 mesh mica iron oxide and aluminum powder slurry, and the mass ratio thereof is 2.5:1.

[0145] Comparative Example 4

[0146] The method according to Example 1 is different in that:

[0147] The epoxy resin is bisphenol A epoxy resin; the bisphenol A epoxy resin is bisphenol A liquid epoxy resin; the softening point of the bisphenol A liquid epoxy resin is 16±4° C., and its model is YPE6101 produced by Shanghai Yuanbang Resin Factory.

[0148] Comparative Example 5

[0149] The method according to Example 1 is different in that:

[0150] The epoxy resin is a bisphenol A epoxy resin; the bisphenol A epoxy resin is a bisphenol A solvent-diluted epoxy resin, the softening point of the bisphenol A solvent-diluted epoxy resin is 68±8°C, and its model is YPE-011X75 produced by Shanghai Yuanbang Resin Factory.

[0151] Comparative Example 6

[0152] The method according to Example 1 is different in that:

[0153] The preparation method of the flake material is:

[0154] S1, under N2 protection, mixed methyl methacrylate, dopamine methacrylamide, N,N-dimethylformyl and initiator in a mass ratio of 1:0.55:18:0.15, and then reacted at 75°C for 5 hours to obtain a prepolymer;

[0155] S2 Mix inorganic non-metallic flake materials (600 mesh glass flakes and 800 mesh graphite flake powder in a weight ratio of 1:0.35), metal flake materials (400 mesh mica iron oxide and aluminum powder slurry in a mass ratio of 2.5:1), N,N-dimethylformyl, and 0.25 mol / L phosphoric acid aqueous solution, react at 75°C for 2 hours, then add prepolymer and heat to 160°C to react for 50 minutes, then cool, filter, and dry to constant weight to obtain flake material.

[0156] Comparative Example 7

[0157] The method according to Example 1 is different in that:

[0158] The anti-rust pigment is 1000 mesh zinc powder.

[0159] Comparative Example 8

[0160] The method according to Example 1 is different in that:

[0161] The preparation method of the flake material is:

[0162] S1, under N2 protection, mixed butyl acrylate, dopamine methacrylamide, N,N-dimethylformyl and initiator in a mass ratio of 1:0.55:18:0.15, and then reacted at 75°C for 5 hours to obtain a prepolymer;

[0163] S2: Mix the inorganic non-metallic flake material, N,N-dimethylformyl and 0.25 mol / L phosphoric acid aqueous solution, and then react at 75°C for 2 hours, then add the prepolymer, heat to 160°C and react for 50 minutes, then cool, filter and dry to constant weight to obtain the flake material;

[0164] The mass ratio of the inorganic non-metallic flake material, N,N-dimethylformyl, 0.25 mol / L phosphoric acid aqueous solution and prepolymer is 10:30:20:100.

[0165] Comparative Example 9

[0166] The method according to Example 1 is different in that:

[0167] The preparation method of the flake material is:

[0168] S1, under N2 protection, mixed butyl acrylate, dopamine methacrylamide, N,N-dimethylformyl and initiator in a mass ratio of 1:0.55:18:0.15, and then reacted at 75°C for 5 hours to obtain a prepolymer;

[0169] S2: Mix the metal type flake material (400 mesh mica iron oxide and aluminum powder slurry, with a mass ratio of 2.5:1), N,N-dimethylformyl, and 0.25 mol / L phosphoric acid aqueous solution, react at 75°C for 2 hours, then add the prepolymer and heat to 160°C for 50 minutes, then cool, filter, and dry to constant weight to obtain the flake material;

[0170] The mass ratio of the metal flake material, N,N-dimethylformyl, 0.25 mol / L phosphoric acid aqueous solution and prepolymer is 10:30:20:100.

[0171] Test Case

[0172] The components A and B in the embodiment and the comparative example were respectively mixed in a mass ratio of 5:1, stirred evenly, and matured for 10-15 minutes to obtain the respective coatings, which were used up within 4 hours.

[0173] The rusted steel plate was treated with Sa2.5 surface treatment and the dry film thickness of the spray paint was 120 microns.

[0174] The test method and results are shown in Table 2-3.

[0175] Table 2

[0176]

[0177]

[0178]

[0179] Table 3

[0180]

[0181]

[0182] From the test results, it can be seen that the coating of the present invention not only has excellent anti-corrosion performance, but also has strong coating film adhesion (MPa), good impact resistance and chemical resistance, and the product has a high solid content.

[0183] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high-solid flake heavy-duty anticorrosion coating for buried metal components, characterized in that: The coating comprises component A and component B; The component A comprises the following components by mass fraction: 30-50% epoxy resin, 10-30% anti-rust pigment, 10-30% flake material, 5-15% filler, 0-10% additive A, and the balance is solvent A; The B component includes the following components by mass fraction: 50-70% of curing agent, 0-15% of auxiliary agent B, and the balance of solvent B; The anti-rust pigment comprises zinc powder, ferrophosphorus powder, zinc phosphate, zinc strontium phosphate and aluminum tripolyphosphate; the mass ratio of zinc powder, ferrophosphorus powder, zinc phosphate, zinc strontium phosphate and aluminum tripolyphosphate is 1: (0.1-0.5): (0.1-0.5), (0.3-0.7): (0.2-0.6); The epoxy resin is a bisphenol A epoxy resin; the bisphenol A epoxy resin includes a bisphenol A liquid epoxy resin and a bisphenol A solvent-diluted epoxy resin; The mass ratio of the bisphenol A type liquid epoxy resin to the bisphenol A solvent-diluted epoxy resin is 1:(0.5-1.5); the difference in softening point between the bisphenol A type epoxy resin and the bisphenol A solvent-diluted epoxy resin is 20-60° C.; wherein the bisphenol A solvent-diluted epoxy resin refers to a semi-solid epoxy resin or a solid epoxy resin dispersed in a corresponding solvent; The flake material includes a modified product of an inorganic non-metallic flake material and a modified product of a metallic flake material; The preparation method of the modified product of inorganic non-metallic flake material and the modified product of metallic flake material is as follows: S1, under N2 protection, mixes acrylic acid monomer, dopamine methacrylamide, N,N-dimethylformyl and initiator, and then reacts at 70-80°C for 4-6 hours to obtain a prepolymer; S2: Mix inorganic non-metallic flake material, metallic flake material, N,N-dimethylformyl and 0.2-0.5 mol / L phosphoric acid aqueous solution, and then react at 70-80°C for 1-3 hours, then add prepolymer and heat to 150-160°C and react for 30-60 minutes, then cool, filter and dry to constant weight to obtain.

2. The coating according to claim 1, characterized in that The filler is selected from at least one of quartz powder, heavy calcium powder, talcum powder, barium sulfate, titanium dioxide and titanium dioxide; the curing agent is selected from aliphatic amine epoxy curing agent and / or polyamide epoxy curing agent; the auxiliary agent A and the auxiliary agent B are each independently selected from at least one of a coupling agent, an anti-settling thixotropic agent, a dispersant, an anti-ultraviolet auxiliary agent and an accelerator; the solvent A and the solvent B are each independently selected from at least one of a reactive diluent, an aromatic hydrocarbon solvent and an alcohol solvent.

3. A method for preparing a high-solid flake heavy-duty anticorrosion coating for buried metal components as claimed in any one of claims 1 to 2, characterized in that: The preparation method comprises: (1) Solvent A is divided into two parts, and the mass ratio of the first part to the second part is (3-4):

1. The first part of solvent A, epoxy resin, anti-rust pigment, flake material, filler, and additive A are dispersed and then sand-milled to a particle size of ≦50 μm, and then the sand-milling dispersion is stopped, and then the second part of solvent A is added and mixed to obtain component A; (2) The curing agent, the auxiliary agent B and the solvent are dispersed for the second time, and then filtered using a 100-150 mesh filter to obtain component B.

Citation Information

Patent Citations

  • Method for improving corrosion resistance of metal component

    CN113045950A